DESAIN DAN IMPLEMENTASI MESIN COMPUTER NUMERICAL CONTROL (CNC) BERBASIS ARDUINO SEBAGAI PLOTTER UNTUK MENGGAMBAR GARIS DAN BIDANG SEDERHANA - Nugroho, Hafidz; Sumariyah, Sumariyah (BERKALA FISIKA, 2019)
The aim of this research is to design and to implement a computer numerical control (CNC) machine using a cellular phone through bluetooth networks for drawing on a two-dimensional (2D) area of 40 mm x 40 mm. The machine consisted of several main parts, including DVD motor stepper, L293D, servo motor, HC-05, and cellular phone. The control was carried out by using the Blynk application that can be used in two modes, namely automatic (G-code based) and manual modes. The capability of the machine to draw test images were carried out, including linear motion, circular motion, up and down motion, displaying menu, rectangle shape, triangle shape, and circular shape. Results show that the CNC machine can move to draw images according to the commands given in each command mode.Keywords: CNC, Cellular phone, Bluetooth, Blynk